THE INFLUENCE OF WORK ETHIC AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE AT PT. BTN (PERSERO) MEDAN BRANCH OFFICE - Mina Indryani Nainggolan; Onan Marakali Siregar (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2023)
This study aims to analyze the influence of work ethic on employee performance, ascertain the impact of organizational commitment on employee performance, and determine the combined influence of work ethic and organizational commitment on employee performance. The research is of a quantitative nature with an associative approach. The study's population consists of employees at PT. Bank Tabungan Negara (Persero) Tbk Medan Branch Office. Simple random sampling was employed to select a sample of 61 respondents. The findings reveal that the work ethic variable (X1) significantly affects employee performance, as does organizational commitment (X2). Work ethic and organizational commitment collectively influence employee performance. The determination test yielded a correlation coefficient (R) value of 0.661, indicating a relatively strong relationship between work ethic, organizational commitment, and employee performance. The adjusted R-square value, or coefficient of determination, suggests that 41.7% of employee performance variance can be explained by work ethic and organizational commitment variables, while the remaining 58.2% is influenced by other unexamined variables.